2017
DOI: 10.18176/jiaci.0137
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Allergy to Mollusks: A Clinical-Immunological Study in a Population From the North of Spain

Abstract: Background: Allergy to mollusks has been the focus of fewer studies than allergy to crustaceans. Furthermore, allergy to mollusks is less well characterized. Objectives: To describe the clinical characteristics of mollusk-allergic patients, to identify the responsible allergens, and to assess crossreactivity. Methods: We performed a prospective multicenter study including 45 patients with mollusk allergy, which was diagnosed based on a suggestive clinical history and a positive skin test result with the agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Spot no 6 was identified as actin, which is an essential component of cell cytoskeleton and participates in many important cellular processes, including cell motility, cell division, various plant cell signalling events etc. Actin was earlier reported as a major allergen from molluscs ( Mohamad-Yadzir et al., 2015 ; Azofra et al., 2017 ; González-Mancebo et al., 2019 ), which is recently reported as a cross-reactive allergen ( Barbarroja-Escudero et al., 2019 ). However, no report was available on the allergenic nature of this protein of plant origin.…”
Section: Discussionmentioning
confidence: 93%
“…Spot no 6 was identified as actin, which is an essential component of cell cytoskeleton and participates in many important cellular processes, including cell motility, cell division, various plant cell signalling events etc. Actin was earlier reported as a major allergen from molluscs ( Mohamad-Yadzir et al., 2015 ; Azofra et al., 2017 ; González-Mancebo et al., 2019 ), which is recently reported as a cross-reactive allergen ( Barbarroja-Escudero et al., 2019 ). However, no report was available on the allergenic nature of this protein of plant origin.…”
Section: Discussionmentioning
confidence: 93%
“…Approximately 45% of individuals with a crustacean allergy are also allergic to mollusk, while 70–80% of mollusk-allergic patients also experienced allergic reactions to crustaceans [ 24 , 30 , 106 , 107 , 108 ]. Some patients may have species-specific shrimp allergy [ 44 , 109 ].…”
Section: Cross-reactivitymentioning
confidence: 99%
“…However, recent studies seem to suggest that this is not the case; in fact, a significant proportion of crustacean allergic patients report that they usually tolerate other invertebrates. 9 Both in vivo and in vitro diagnostics failure nowadays is caused in part by the poor quality of the extracts, and extract-based diagnostics can also be limited by cross-reactivity, failing to detect IgE crosslinking. 10,11 It has been widely demonstrated that diagnostics with commercially available shellfish extracts do not always lead to the correct identification of sensitized patients.…”
Section: Introductionmentioning
confidence: 99%